The glycosylation pattern of common allergens: the recognition and uptake of Der p 1 by epithelial and dendritic cells is carbohydrate dependent - Al-Ghouleh, Abeer; Johal, Ramneek; Sharquie, Inas K.; Emara, Mohamed; Harrington, Helen; Shakib, Farouk; Ghaemmaghami, Amir M. (Public Library of Science, 2012)
Allergens are initiators of both innate and adaptive immune responses. They are recognised at the site of entry by epithelial and dendritic cells (DCs), both of which activate innate inflammatory circuits that can collectively induce Th2 immune responses. In an attempt to have a better understanding of the role of carbohydrates in the recognition and uptake of allergens by the innate immune system, we defined common glycosylation patterns in major allergens. This was done using labelled lectins and showed that allergens like Der p 1 (Dermatophagoides pteronyssinus group 1), Fel d 1 (Felis domisticus), Ara h 1 (Arachis hypogaea), Der p 2 (Dermatophagoides pteronyssinus group 2), Bla g 2 (Blattella germanica) and Can f 1 (Canis familiaris) are glycosylated and that the main dominant sugars on these allergens are 1–2, 1–3 and 1–6 mannose. These observations are in line with recent reports implicating the mannose receptor (MR) in allergen recognition and uptake by DCs and suggesting a major link between glycosylation and allergen recognition. We then looked at TSLP (Thymic Stromal Lymphopoietin) cytokine secretion by lung epithelia upon encountering natural Der p 1 allergen. TSLP is suggested to drive DC maturation in support of allergic hypersensitivity reactions. Our data showed an increase in TSLP secretion by lung epithelia upon stimulation with natural Der p 1 which was carbohydrate dependent. The deglycosylated preparation of Der p 1 exhibited minimal uptake by DCs compared to the natural and hyperglycosylated recombinant counterparts, with the latter being taken up more readily than the other preparations. Collectively, our data indicate that carbohydrate moieties on allergens play a vital role in their recognition by innate immune cells, implicating them in downstream deleterious Th2 cell activation and IgE production.